What is the relationship between democracy and development according to policies of aid conditionality as implemented in Africa? - George, Emma Lavinia (My University, 2015)
This research project looks at the relationship between democracy and development according to policies of aid conditionality in Africa. This involves an analysis of major donors, mainly international financial institutions such as the IMF and World Bank as well as bilateral donors, and the evolution of aid conditionality through the theoretical framework of liberal internationalism. This research focuses on both economic and political conditionality but reveals that economic interests are at the heart of conditionality and are always prioritized over political development. This has important implications for democracy and development because development discourse has identified key correlations between the principles of good governance promoted by a democratic system and development. Through an examination of two African case studies, this research shows that aid conditionality, with its emphasis on neoliberal, free-market economic adjustment, has not fostered adequate development with many recipients of such aid qualifying for the Heavily Indebted Poor Countries initiative that provides debt relief in the interest of poverty reduction. Looking forward, sustainable development can only be achieved with equal dedication to all its spheres; political, economic, and social, thereby providing an adequate foundation for increased international cooperation.
This thesis is in partial fulfillment of a Master of Arts by Coursework and Research Report in International Relations and has been approved by the University of the Witwatersrand.
Keywords: Democracy; Politics and government; Africa|